2003
DOI: 10.1086/375301
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian Galactic Plane Survey

Abstract: The Canadian Galactic Plane Survey (CGPS) is a project to combine radio, millimetre and infrared surveys of the Galactic Plane to provide arc-minute scale images of all major components of the interstellar medium over a large portion of the Galactic disk. We describe in detail the observations for the low-frequency component of the CGPS, the radio surveys carried out at the Dominion Radio Astrophysical Observatory (DRAO), and summarize the properties of the merged database of surveys that comprises the CGPS.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
560
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 558 publications
(585 citation statements)
references
References 33 publications
11
560
0
3
Order By: Relevance
“…However, no radio emission has been detected from the AXP. The analysis of CO observations (Tatematsu et al 1987;Kothes et al 2002;Taylor et al 2003) has revealed that the western part of the SNR has encountered a giant molecular cloud (GMC) complex, resulting in a semicircular shape of the remnant. Moreover, in radio a double-shell structure can be seen (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no radio emission has been detected from the AXP. The analysis of CO observations (Tatematsu et al 1987;Kothes et al 2002;Taylor et al 2003) has revealed that the western part of the SNR has encountered a giant molecular cloud (GMC) complex, resulting in a semicircular shape of the remnant. Moreover, in radio a double-shell structure can be seen (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recent measurements show that the distance to CTB 109 lies between 3 and 4 kpc (Kothes et al 2002;Tian et al 2010); the latest value is 3.2 ± 0.2 kpc (Kothes & Foster 2012). It is even more difficult to determine the proper motion of A&A 582, A47 (2015) (Kothes et al 2002) from the Canadian Galactic Plane Survey (CGPS, Taylor et al 2003). Right: intensity map (0.3−4.0 keV) of CTB 109 in false colour from the XMM-Newton EPIC data (Sasaki et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…21cm line data from the Canadian [12], Southern [8], and VLA [13] Galactic Plane Survey components of the IGPS reveal a rich and subtle population of HISA features, many of which are invisible at lower resolutions. Analyses of several CGPS and SGPS features [4,6,7] find temperatures of a few tens of Kelvins and densities of order ¡ cm5 7 6 .…”
Section: Hisa In the Galactic Planementioning
confidence: 99%
“…In this paper, we use the 1420 MHz radio continuum image of the WR 130 area from the Canadian Galactic Plane Survey (CGPS - Taylor et al 2003). Because this image is the result of a mosaic containing more than one pointing field, it has a slightly better signal-to-noise ratio and dynamic range.…”
Section: Observationsmentioning
confidence: 99%